Students and sports : the association between participation in sports and academic achievement : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, College of Education, Albany, New Zealand - Prasad, Vibha V (Massey University, 2012)
Previous studies have found that participation in sports is positively associated with academic achievement for students. Due to the lack of studies in the New Zealand context and few studies examining Intermediate School students, the purpose of the current study was to examine the associations between the level of participation in sports and mean grades for Intermediate students. Data were obtained from self-report measures on sports participation and academic achievement. These data were gathered via anonymous questionnaires which were completed by students (n=86) from two different Intermediate Schools in Auckland. Results from the Independent Samples T-Tests revealed that male sports participants achieved significantly higher mean grades overall; and higher maths grades, than male non-sports participants. Further, and not surprisingly, sports participants from the high decile school achieved higher grades than students from the lower decile school. Simple Linear Regression revealed that the frequency of sports played per week was positively associated with mean grades. Results were therefore consistent with previous studies confirming the value of sports participation.
Keywords: School sports; Middle school athletes; School children; Academic achievement; Intermediate school pupils; New Zealand